Research on Layout Planning of the Integrative Passenger Transit Transfer Hub in City - Jia, Hua Fei; Wu, Jun; Li, Cheng Bing; Chen, Wei Dong (Applied Mechanics and Materials, 2013)
In the background of the integration, how to scientifically and reasonably distribute transfer hub becomes the problem urgent to be solved for traffic experts. First of all, this paper puts forward research ideas; second, it expounds the influence factors of layout planning of the integrative passenger transit transfer hub in city, before transfer hub site evaluation, we first establish the selections of transfer hub distribution, and on this basis, evaluation index system of the integrative transfer hub layout is built; after this, a entropy weight-based extension decision model is set up by application of the dynamic multiple valued background principle and the rough set theory; finally, taking the Haidian District of Beijing as an example, the model and algorithm of the subject are validated.